Condições de vida e de saúde, e consumo de alimentos segundo a vulnerabilidade à saúde no programa academia da saúde de Belo Horizonte-MG - Priscila Lenita Candida dos Santos (2022)
INTRODUCTION: Changes in the dietary patterns of the world population have been observed in recent years. In Brazil, it was no different, there was a reduction in the consumption of fresh and minimally processed foods, in parallel with the increase in processed and ultra-processed foods (UPF). Such changes are not random and can be associated with social and health inequalities, including the vulnerability of the area in which one lives and circulates. OBJECTIVE: To analyze living and health conditions; and food consumption and its association with health vulnerability among participants of the Academia da Saúde Program (PAS) in Belo Horizonte, Minas Gerais. METHODS: Cross-sectional study conducted with a simple cluster sample of PAS units, stratified by the regions of the municipality. In the 18 units of the PAS sampled, all individuals aged 20 years or more frequently in the service were interviewed. Sociodemographic data, living and health conditions (referred morbidities); perception of health and quality of life; smoking habit; time of participation in the PAS; and nutritional status according to the Body Mass Index (BMI). Food consumption was obtained by the average of two 24-hour food recalls (R24h) and categorized according to the NOVA classification in: culinary preparations (unprocessed or natural and minimally processed foods, and processed culinary ingredients), processed foods and UPF. To assess vulnerability, the Health Vulnerability Index (HVI) was used, a composite indicator that makes it possible to identify unequal and unfavorable areas for health through the assessment of access to housing, urban infrastructure, education, health services, security and income; being classified in: low, medium, high/high. RESULTS: Of the 3,056 participants, most were women (87.8%) with a median age of 58 years. Individuals residing in more vulnerable areas were younger (median: 56 years); had less schooling (median: 5 years of study) and income (median: R$600.00); longer participation in the PAS (median: 17.9 months); and were from economic classes D/E (68.1%). Regarding health conditions, 74.0% of the participants considered their health as very good/good, with this prevalence being lower among individuals who lived in areas with high/very high SVI (71.5%; p=<0.001); and 40.2% were overweight, with a higher prevalence among those living in areas with a medium SVI (40.6%; p= 0.022). The average energy consumption was 1,429.7 kcal, coming mainly from culinary preparations (61.6%) and AUP (27.4%). After adjustments, it was found that individuals residing in areas with high/very high SVI had higher consumption of culinary preparations (β= 3.4; 95%CI: 1.6; 5.3) and lower UPA consumption (β=- 2.7; 95%CI: -4.6; -0.8), when compared to those with low SVI. CONCLUSION: PAS participants who lived in more vulnerable areas of the city had worse living and health conditions, however, they had lower consumption of UPF and higher consumption of culinary preparations. These results point to the need for actions to promote adequate and healthy food, differentiated according to the vulnerability of the territory, with special attention to the less vulnerable areas.